Analisis Pengaruh Current Ratio, Price Earning Ratio, Return On Asset Dan Debt To Equity Ratio Terhadap Nilai Perusahaan - Silvia Indrarini; Julinar Tryane Kobar (Universitas Katolik Widya Karya Malang, 2022)
This study aims to determine the influence analysis of the Current Ratio (CR), Price Earning Ratio (PER), Return On Assets (ROA) and Debt To Equity Ratio (DER) on company value in plastic and packaging companies for the 2016-2020 period. This type of research is explanatory research. The population in this study were 15 plastic and packaging companies listed on the Indonesia Stock Exchange for the 2016-2020 period, the sample was selected using the purposive sampling method, 5 companies were obtained. The results of multiple linear regression analysis show that CR, PER, ROA and DER simultaneously affect the value of plastic and packaging companies listed on the IDX for the 2016-2020 period. Partially, PER, ROA and DER have a positive and significant effect on firm value, while CR has no effect on firm value. The variable that has the most dominant effect is PER.